Utilization of android-based paediatric assessment triangle application as an emergency detection tool for children - Dessie Wanda; La Ode Abdul Rahman; Efa Apriyanti; Permaida; Yayah; Titik Ambar Asmarini; Indah Reski Amallia; Ina Yuhana; Ricca Olivia Nastasya (Journal of the Pakistan Medical Association, 2024)
Objective: To identify the effectiveness of an android-based paediatric assessment triangle application in emergency diagnostics. Method: The action research study was conducted in the emergency department of a hospital under the Ministry of Defence, Indonesia, located within the Ministry of Defence Rehabilitation Centre Complex, from April to December 2020 after approval from the ethics review committee of the Faculty of Nursing, Universitas Indonesia, Indonesia, employing quantitative and qualitative methods consisting of planning, acting, observing and reflecting stages. Emergency department nurses with at least D3 nursing graduation who were able to identify emergency status in children were included. The subjects were given training on paediatric assessment triangle application before using it in their professional life. The difference was noted through pre- and post-intervention tests. Qualitative data was collected using focus group discussion and system usability scale. Results: Of the 9 nurses, 5(55.6%) were males, 4(44.4%) were females, 8(88.9%) were aged 26-35 years, and 2(22.2%) had professional experience 1-2 years. The mean baseline score was 36.1±11.4, while the mean post-intervention score was 70.9±14.4. The fastest application completion time was 13 seconds, while the slowest was 52 seconds. Qualitative data led to the emergence of 4 themes: time required to complete the application; preference for connectivity with the hospital’s electronic record system; assessment of children’s clinical status; and, unfamiliarity with the computerised system. The mean system usability scale score was 72.22±11.35 (range: 52.5-92.5). Conclusion: Paediatric assessment triangle application could be a valid tool for identifying emergency severity in patients during the triage process. Keywords: Android, Application, Paediatric Assessment Triangle, PAT, Paediatric emergency.